Modification of Boc-Protected CAN508 via Acylation and Suzuki-Miyaura Coupling - Pisár, Martin (Molecules, 2018)
The cyclin-dependent kinase inhibitor, CAN508, was protected with di-tert-butyl dicarbonate to access the amino-benzoylated pyrazoles. The bromo derivatives were further arylated by Suzuki-Miyaura coupling using the XPhos Pd G2 pre-catalyst. The coupling reaction provided generally the para-substituted benzoylpyrazoles in the higher yields than the meta-substituted ones. The Boc groups were only utilized as directing functionalities for the benzoylation step and were hydrolyzed under conditions of Suzuki-Miyaura coupling, which allowed for elimination of the additional deprotection step.